Competências profissionais em vendas: um estudo no subsetor de comércio atacadista de alimentos de Fortaleza-CE - Costas, Mário Helder Lopes (2024)
As in other areas, in the food sector, the sales force constitutes the most direct form of communication between the organization and its customers. Salespeople's skills are fundamental in sales management, requiring specific knowledge, skills and attitudes to achieve success in an increasingly dynamic market, thus being an important competitiveness factor. In light of this, this study aims to investigate sales skills in the food sector in the State of Ceará, by mapping knowledge, skills and attitudes. The research is characterized as quali-quanti and descriptive. Data collection took place through the application of a questionnaire and an interview guide, with the data analyzed, respectively, using descriptive statistics and content analysis techniques. The results show that, regarding sales knowledge, sales managers expect sales professionals to have broad knowledge, capable of planning strategies, interpreting market signals, understanding customer needs and developing trusting relationships. As for skills, they presented the greatest divergence between the perspective of salespeople and that of managers, given that managers require more practical and continuous training to qualify the sales force. As for attitudes, the reports showed that ethics, commitment and trust are pillars that showed greater concern on the part of managers, and should be developed and demanded.